A multi-technique investigation of sulfur grain boundary segregation in nickel - Allart, M; Christien, F; Le Gall, R; Nowakowski, P; Grovenor, C (2013)
The grain boundary segregation (GBS) of sulfur in nickel was studied using Auger electron spectroscopy (AES) and wavelength-dispersive X-ray spectroscopy (WDS), and a linear correlation between the two techniques was demonstrated. The kinetics and thermodynamic parameters of sulfur GBS were determined. The discrepancy between the AES/WDS results obtained here and those from a previous study on the same material undertaken using secondary ion mass spectroscopy was interpreted in terms of the selection of grain boundary type by the sample preparation method. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.